Interaction Between Serotonin Transporter Polymorphism (5-HTTLPR) and Stressful Life Events in Adolescents’ Trajectories of Anxious/Depressed Symptoms - Petersen, Isaac T. (2012)
Caspi et al. (2003) found an interaction between the serotonin transporter polymorphism gene (5-HTTLPR) and stressful life events on depression. Subsequent attempts to replicate have been inconsistent. The present research included long allele variants modified by SNP rs25531 and tested the interaction on adolescents’ trajectories of anxious/depressed symptoms, with consideration of possible age effects. Adolescents (N = 574), of whom 436 were genotyped, were followed from ages 12 to 17. Analyses demonstrated a G × E interaction in predicting the development of anxious/depressed symptoms. Specifically, adolescents with lower serotonin transcriptional efficiency (TE) genotypes whose mothers reported more stressful events were reported to show more anxious/depressed symptoms and greater increases in the development of symptoms of anxiety and depression than were higher TE adolescents, particularly at ages 16 and 17. Interactions did not differ by gender. Findings demonstrate that stress may affect adolescents’ likelihood of experiencing anxious/depressed symptoms when they have a low serotonin TE (A/G-modified 5-HTTLPR) genotype and suggest that the vulnerability may be stronger in late than early adolescence.